Environmental policy failure : the Australian story - Crowley, Kate.; Walker, K. J. 1940- (Tilde University Press, 2012)
Demonstrates Australia's environment is under unprecedented stress, which is now all too real in terms of problems such as rising sea levels, catastrophic bush fires, drought and dying river systems. The book reveals the nature of environmental policy failure.